CHEMICAL INFORMATION FROM GC-MS STUDIES OF METHANOLIC LEAF EXTRACT OF ANDROGRAPHIS PANICULATA AND DATURA METEL AND THEIR ANTIBACTERIAL ACTIVITY AGAINST ISOLATED PSEUDOMONAS AERUGINOSA (PB112) STRAIN - SOMERITA PANDA; P.K.BANDYOPADHYAY (International Journal of Pharma and Bio Sciences, 2013)
The present study was carried out to determine the phytochemical profile and antibacterial activity of Andrographis paniculata and Datura metel extracts. For the present investigation, extracts of A. paniculata and D.metel were prepared by extraction in methanol, chloroform, acetone and benzene and were compared for their antibacterial activity. The antibacterial activities were assessed by measuring the diameter of the inhibition zones by Disc diffusion method. In comparison to this different extracts, the methanol extract showed better antibacterial activity against the isolated P.aeruginosa bacterial strain tested. The chemical composition of methanol extracts of these two plants were investigated by GC-MS, while the mass spectra of the compounds found in the extract was matched with the NIST and WILEY library.